RESPON PERTUMBUHAN TANAMAN TOMAT (SOLANUM LYCOPERSICUM ) DENGAN PEMBERIAN PUPUK BOKASHI KOTORAN AYAM BROILER - Mefiruti Sihura (Jurnal Sapta Agrica, 2022)
The research method used is a quantitative research method with a pure experimental method (True Experiment) with a Completely Randomized Design consisting of six treatments and five replications. The research population was tomato (Solanum lycopersicum) as many as 30 plants. The sample in this study were 30 tomato plants. The research sample was selected using simple random sampling. The research data were analyzed using the SPSS 20 application consisting of the Normality Test, Homogeneity Test, and Hypothesis Testing. The research findings obtained indicate that there is a response to tomato plant growth by giving broiler chicken manure bokashi fertilizer both on tomato plant height (Solanum lycopersicmu) and on tomato plant leaf blade (Solanum lycopersicum). tomato plant (Solanum lycopersicum) and can be used as an alternative to replace inorganic fertilizers (chemical fertilizers) which can affect soil quality if used continuously. The suggestion offered by the researcher is that the use of broiler chicken manure bokashi fertilizer can be further increased to reduce the use of inorganic fertilizers.